PENGARUH JENIS KELAMIN DAN BOBOT POTONG TERHADAP KINERJA PRODUKSI DAGING DOMBA LOKAL EFFECT OF SEX AND SLAUGHTER WEIGHT ON THE MEAT PRODUCTION OF LOCAL SHEEP - Endah Subekti Subekti (Universitas Wahid Hasyim, 2007)
The research was conducted to determine the effect of sex and slaughter weight on the meat production. Increasing slaughter weight of male sheep and female sheep always was followed increasing carcass weight. At the same slaughter weight, male sheep had weight and percentage carcass were higher than female sheep. The statistical analysis resulted showed that sex was very significant effect, and slaughter weight was no significant effect, but there were interaction between sex and slaughter weight on fat, percentage fat, pelvic, kidney fat and yield grade number. Key words : sex, slaughter weight, meat production, local sheep